Pengaruh Prokrastinasi Akademik dan Motivasi Belajar Terhadap Prestasi Belajar Matematika Siswa Sekolah Dasar di Gugus Jenderal Sudirman Kecamatan Wuryantoro - Indriyati, Agustina; Indriayu, Mintasih; Prastiti, Tri Dyah (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of this study was to analyze the effect of academic procrastination and learning motivation on mathematics learning achievement. The location of the research was carried out at the Gugus Jenderal Sudirman Wuryantoro Elementary School. The population in this study were 37 grade IV public elementary school students in the Cluster General Sudirman Wuryantoro spread across 5 (five) schools. Data collection using a questionnaire, data analysis using multiple linear regression analysis. The results of the study concluded that academic procrastination has a negative effect on mathematics learning achievement as evidenced by the beta coefficient value of (– 0.336) t count value of (-2.255) with a sig value of 0.031 <0.05. Learning motivation has a positive effect on mathematics learning achievement as evidenced by the magnitude of the beta coefficient of 0.579, with a t-count of 3.317 with a sig value of 0.002 <0.05. Academic procrastination and learning motivation simultaneously affect mathematics learning achievement as evidenced by the F value of 36.309, with sig. of 0.000